Do Muscles Constrain Skull Shape Evolution in Strepsirrhines?. Issue 2 (13th January 2018) - Fabre, Anne‐Claire; Perry, Jonathan M. G.; Hartstone‐Rose, Adam; Lowie, AuróLien; Boens, Andy; Dumont, MaÏtena
ABSTRACT: Despite great interest and decades of research, the musculoskeletal relationships of the masticatory system in primates are still not fully understood. However, without a clear understanding of the interplay between muscles and bones it remains difficult to understand the functional significance of morphological traits of the skeleton. Here, we aim to study the impacts of the masticatory muscles on the shape of the cranium and the mandible as well as their co‐variation in strepsirrhine primates. To do so, we use 3D geometric morphometric approaches to assess the shape of each bone of the skull of 20 species for which muscle data are available in the literature. Impacts of the masticatory muscles on the skull shape were assessed using non‐phylogenetic regressions and phylogenetic regressions whereas co‐variations were assessed using two‐blocks partial least square (2B‐PLS) and phylogenetic 2B‐PLS. Our results show that there is a phylogenetic signal for skull shape and masticatory muscles. They also show that there is a significant impact of the masticatory muscles on cranial shape but not as much as on the mandible. The co‐variations are also stronger between the masticatory muscles and cranial shape even when taking into account phylogeny. Interestingly, the results of co‐variation between the masticatory muscles and mandibular shape show a more complex pattern in two different directions to get strong muscles associated with mandibular shape: a folivore way (with the bamboo lemurs and sifakas) and a hard‐object eater one (with the aye‐aye). Anat Rec, 301:291–310, 2018. © 2018 Wiley Periodicals, Inc.